The Urgency of Ahlus Sunnah wal Jamaah Based Islamic Jurisprudence in Maintaining Cohesiveness of the Indonesian Republic - Jafar, Wahyu Abdul; Asmara, Musda (Al-Istinbath: Jurnal Hukum Islam, 2022)
This study aims to determine the urgency of Ahl as-Sunnah wal-Jamaah Based Islamic Jurisprudence in Maintaining Cohesiveness of the Indonesian Republic. This study is literature research, which uses documentation techniques in collecting research data. At the same time, the analysis technique used in this research is the descriptive inductive technique. After conducting in-depth research, a conclusion was found that ahlus sunnah wal jamaah Based Islamic Jurisprudence is urgently disseminated and practiced. Ahlus sunnah wal jamaah Based Islamic Jurisprudence can be a strong binder of unity and integrity because there are ahlus sunnah wal jamaah Based Islamic Jurisprudence values of hubul wathon (love of the homeland), unity, and tolerance among religious believers. This teaching is more accepting of the differences in the broader community than radical and liberal Islam teachings, which divide the unity among Muslims and often create commotion and quarrels in society. Ahl as-Sunnah wal-Jamaah Based Islamic Jurisprudence can block Islamic sharia that deviates and leaves the corridor of the principle of tasriul ahkam, namely realizing the benefit of human life. The benefit will be easily realized if in a country the people are united, in harmony, live in peace, and are not hostile to each other.